High polarization, endurance and retention in sub-5 nm Hf0.5Zr0.5O2 films. Issue 20 (18th May 2020) - Lyu, Jike; Song, Tingfeng; Fina, Ignasi; Sánchez, Florencio
Abstract : High polarization, endurance and retention are reached in epitaxial Hf0.5 Zr0.5 O2 films as thin as sub-5 nm. Abstract : Ferroelectric HfO2 is a promising material for new memory devices, but significant improvement of its important properties is necessary for practical application. However, previous literature shows that a dilemma exists between polarization, endurance and retention. Since all these properties should be simultaneously high, overcoming this issue is of the highest relevance. Here, we demonstrate that high crystalline quality sub-5 nm Hf0.5 Zr0.5 O2 capacitors, integrated epitaxially with Si(001), present combined high polarization (2 P r of 27 μC cm −2 in the pristine state), endurance (2 P r > 6 μC cm −2 after 10 11 cycles) and retention (2 P r > 12 μC cm −2 extrapolated at 10 years) using the same poling conditions (2.5 V). This achievement is demonstrated in films thinner than 5 nm, thus opening bright possibilities in ferroelectric tunnel junctions and other devices.